181 Frameless Neuronavigation With Computer Vision and Real Time Tracking for Bedside External Ventricular Drain Placement: A Cadaveric Study. (1st April 2022) - Robertson, Faith C.; Sha, Raahil; Amich, Jose; Lee, Benjamin; Lal, Avinash; Calvachi, Paola; Wu, Kyle; Gormley, William; Weaver, James; Tokuda, Junichi
Abstract : INTRODUCTION: A major obstacle to improving ventriculostomy safety and accuracy with image guidance technologies is the lack of a rapidly deployable, real-time registration and tracking system for a moving patient. METHODS: Computer vision technology was used to develop an algorithm for near continuous, automatic, and marker-less image registration. The program fuses a subject's pre-procedure CT scan to live 3D camera images (Snap-Surface), and movement is incorporated by artificial intelligence driven recalibration (Real-Track). Surface registration error (SRE) and target registration error (TRE) were calculated for five cadaver heads that underwent serial movements (fast and slow velocity roll, pitch, and yaw motions), and several test conditions. Six catheters were placed in each cadaver (30 placements). Post-procedure CT scans allowed comparison of planned and actual catheter position for user error calculation. RESULTS: Registration was successful for all five cadaveric specimens (average SRE 0.429 mm, ±0.108). Accuracy of TRE was under 1.2mm throughout specimen movements of low and high velocities of roll, pitch, and yaw movements, with the slowest recalibration time of 0.23 seconds. There were no statistically significant differences in SRE when the specimens were draped or fully undraped (p-value = 0.336). Addition of bright light or performance under dim light did not significantly affect SRE (p-value = 0.742 and 0.859, respectively). Average TRE for catheter placements was 0.862 mm (±0.322), and average user error for the was 1.674 mm (±1.195). CONCLUSION: This computer vision-based registration system provides real-time tracking of cadaveric heads with recalibration time of less than one-quarter of a second with sub-millimetric accuracy, and enabled catheter placements with millimetric accuracy. Using this approach to guide bedside ventriculostomy could reduce complications, improve safety, and could be extrapolated to other frameless stereotactic applications in awake, non-immobilized patients.